Key Amino Acids for Pepper Vein Yellows Virus P0 Protein Pathogenicity, Gene Silencing, and Subcellular Localization - Wang, Lishuang; Tian, Peijie; Yang, Xiuling; Zhou, Xueping; Zhang, Songbai; Li, Chun; Yang, Xuehui; Liu, Yong (Frontiers in Microbiology, 2021)
Pepper vein yellows virus is a newly recognized Polerovirus extracted from Chinese pepper. Symptoms of PeVYV infested pepper plants comprised inter-vein yellow-staining, leaf curl formation and other malformations, leaf internodal shrinking. However, the roles of the viral proteins were as yet undetermined. The P0 protein of genus Polerovirus has established postransciptional gene silencing (PTGS) activity. This investigation focused on PeVYV-encoded P0 protein, that was scrutinized for possible virulence capacity, PTGS activity and tendencies to localize in the nucleus. This study revealed that P0 influenced the pathogenic properties of a specific heterologous potato virus X. In addition, P0 proteins impaired local gene silencing, though do not regulate generalized gene silencing within Nicotiana benthamiana 16c plants. Furthermore, P0 proteins localized mainly in the nucleus, particularly in the nucleolus. P0 deletion mutagenesis demonstrated that the F-box motif (56-72 amino acids, AAs) were essential for P0 symptom determination, inhibition of PTGS, as well as subcellular localization. F-box motif mutation analysis indicated that AA 57 of P0 protein was pivotal site in symptom developments, and AA 56 of P0 protein was indispensable for inhibiting PTGS and subcellular localization.